CORRELATION BETWEEN DAILY SODIUM INTAKE AND SYSTOLIC BLOOD PRESSURE IN ELDERLY PATIENTS WITH ESSENTIAL HYPERTENSION - Basudewa, I Nyoman Arhi; Setyawan, Yuswanto (LPPM Univ. Ibn Khaldun Bogor, 2025)
Hypertension remains a major global public health problem, particularly among the elderly. This study aims to analyze the correlation between daily sodium intake and systolic blood pressure in older adults with essential hypertension. A cross-sectional study was conducted on 127 elderly respondents using a validated Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess daily sodium intake and a calibrated Omron HEM-7121 digital sphygmomanometer to measure systolic blood pressure. Data were analyzed using Spearman’s rank correlation test. The results showed a significant positive correlation between daily sodium intake and systolic blood pressure (r = 0.423; p < 0.001). Respondents who consumed more than 4000 mg of sodium per day tended to have systolic blood pressure above 160 mmHg. This finding suggests that excessive sodium intake contributes significantly to elevated systolic pressure in elderly individuals with essential hypertension. The study highlights the urgent need for sodium reduction interventions tailored to the elderly population as part of community-based hypertension control programs.